Fitase em dietas deficientes em fósforo, cálcio e sódio para frangos de corte - Scariot , Rovaldo (2019)
An experiment was conducted to evaluate the effect of phytase superdosing on performance, nutrient digestibility, carcass yield and bone quality of broiler chickens submitted to diets with reduced nutritional levels of phosphorus, calcium and sodium and supplemented with phytase enzyme (manufacturer's recommended dosage and superdosing). In the zootechnical performance were observed the productivity standards in feed consumption, average weight, weight gain, feed conversion, bone quality, carcass yield and special cuts and digestibility of the nutrients offered in the diets. The experimental design was completely randomized with four treatments with nine replicates and 43 birds per box, divided into: positive control (CP), with adequate nutritional levels, without addition of enzyme; negative control (CN), with reduction of phosphorus (0.15%), calcium (0.16%) and sodium (0.03%); CN with addition of phytase enzyme 500 FTU kg-1 and CN with addition of phytase enzyme 1000 FTU kg-1. Phytase supplementation (500 and 1000 FTU kg-1) in P, Ca and Na deficient diets resulted in improved performance and carcass yield and commercial cuts of broiler chickens compared to those receiving deficient diets without phytase supplementation. Supplementation of 500 or 1000 FTU kg-1 of phytase to feed resulted in similar values (p>0.05) of apparent metabolizable energy (AME) in diets with reduced levels of P, Na, and Ca compared to a positive control diet. The birds supplemented with phytase had reduced phytate, P and Ca excretion in relation to the control diet. Birds supplemented with 500 or 1000 FTU kg-1 of feed and birds of the positive control showed the same productive performance. Phytase supplementation (FTU and 1000 FTU kg-1) in P, Ca and Na deficient diets resulted in better bone densitometry indices at 21 and 47 days compared to deficient diets. The lowest (p<0.05) bone:cartilage relation was observed in the tibia of the broilers that received the deficient diet at 21 days of age. The birds that consumed diets supplemented with phytase presented higher bone resistance to the break, in relation to the negative control in the whole period of the experiment, but the results were the same those birds fed diets with adequate levels. Birds supplemented with phytase superdosing showed a reduction in femoral bone elasticity at 21 and 47 days, compared to birds of negative control. The inclusion of phytase (500 or 1000 FTU kg-1) in P, Ca and Na deficient diets was effective in re-establishing nutrient levels in the diets, economically and environmentally efficient.